All Days 2004
DOI: 10.2118/91435-ms
|View full text |Cite
|
Sign up to set email alerts
|

Successful Application of Hydrajet Fracturing on Horizontal Wells Completed in a Thick Shale Reservoir

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe evolution of well completions in the Barnett

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 12 publications
(1 reference statement)
1
46
0
1
Order By: Relevance
“…For all the wells, the ISIP values increase moving from the toe to the heel in a steady progression, except that there is a fall-off for the last few stages in Wells A, B, and C. A similar effect has been reported in the gas shale literature and explained as a "stress shadow" related to sequential propped planar fractures (East et al, 2004;Fisher et al, 2004;Soliman et al, 2008;Waters et al, 2009).…”
Section: Isip Escalationsupporting
confidence: 79%
“…For all the wells, the ISIP values increase moving from the toe to the heel in a steady progression, except that there is a fall-off for the last few stages in Wells A, B, and C. A similar effect has been reported in the gas shale literature and explained as a "stress shadow" related to sequential propped planar fractures (East et al, 2004;Fisher et al, 2004;Soliman et al, 2008;Waters et al, 2009).…”
Section: Isip Escalationsupporting
confidence: 79%
“…E. East Jr et al, (2004) system in order to incorporate natural fractures effects in Shale Gas reservoirs. They also considered the decrease of fracture conductivity with the decrease of pore pressure and stress around the hydraulic fracture.…”
Section: Multistage Hydraulic Fracturing In Horizontal Wellsmentioning
confidence: 99%
“…21 gives the match between the observed and calculated production data. East et al (2004), who indicated that those dimensions had been verified using microseismic monitoring, gave the basic dimensions of the fractures. The total length of the horizontal section is 2120 ft, with 20 transverse fractures intersecting it.…”
Section: Field Examplesmentioning
confidence: 99%